2001
DOI: 10.1103/physrevlett.87.078302
|View full text |Cite
|
Sign up to set email alerts
|

Regular Wave Propagation Out of Noise in Chemical Active Media

Abstract: A pacemaker, regularly emitting chemical waves, is created out of noise when an excitable photosensitive Belousov-Zhabotinsky medium, strictly unable to autonomously initiate autowaves, is forced with a spatiotemporal patterned random illumination. These experimental observations are also reproduced numerically by using a set of reaction-diffusion equations for an activator-inhibitor model, and further analytically interpreted in terms of genuine coupling effects arising from parametric fluctuations. Within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 27 publications
2
40
0
Order By: Relevance
“…These results are in Fig. 1 The domains of parameters D and I 0 for excitable and subexcitable systems agreement with those reported in references (Alonso et al 2002;Hou and Xin 2002). If we change the parameters, such that the coupling coefficient D = 0.063 and the external current I 0 = 5, the line wave cannot propagate with time, as shown in Fig.…”
Section: Model and Numerical Simulationsupporting
confidence: 88%
“…These results are in Fig. 1 The domains of parameters D and I 0 for excitable and subexcitable systems agreement with those reported in references (Alonso et al 2002;Hou and Xin 2002). If we change the parameters, such that the coupling coefficient D = 0.063 and the external current I 0 = 5, the line wave cannot propagate with time, as shown in Fig.…”
Section: Model and Numerical Simulationsupporting
confidence: 88%
“…For comparison, ͑aЈ͒ -͑dЈ͒ correspond to the noise-free case with a constant and uniform illumination fixed to the averaged intensity. From Alonso et al, 2001. Actually, the behavior shown in Fig. 37 constitutes a particular example of a whole range of noise-induced transitions linking different excitability regimes, including subexcitable→ excitable ͑the case of Fig.…”
Section: Excitability Transitions: Experimental and Numerical Realizamentioning
confidence: 99%
“…Recently, it was observed that noise can support wave propagations in sub-excitable [20,17,15] systems due to a noise-induced transition [21,22]. In these studied, the medias are static, and transports are governed by diffusion [23].…”
Section: Introductionmentioning
confidence: 99%